GERMINATION AND SEEDLING SURVIVALITY OF RICE (Oryza sativa L.) UNDER ANOXIA (Applied Biological Research, 2023)
A study was conducted at the Stress Physiology Laboratory, AAU,  Jorhat, Assam (India) during kharif season 2016-2017. Rice genotypes  (146 nos.) collected from different ecotypes were screened for anaerobic  tolerance based on their survivality. Of the genotypes evaluated, six  genotypes viz., ‘Ronga Lahi’, ‘Ronga Bao’, ‘Bangali Lahi’, ‘Suwag Moni  Horu’, ‘Asra 123’ and ‘Asra 8’ were selected as anoxia tolerant genotypes on the basis of seed germination, seedling survival and growth. These  genotypes were also evaluated for amylase activity. The result revealed a  significant variation in genotypes during anoxic germination in terms  amylase activity. Higher α- and β-amylase activities were observed in  ‘Asra 123’, followed by ‘Asra 8’ as compared to the susceptible genotype  ‘IR-64’. Increased amylases activity in tolerant genotypes might be  attributed to the production and maintenance of sufficient amount of  soluble sugar under anoxic condition during germination. The study  revealed that ‘Asra 123’, ‘Asra 8’, ‘Ronga Lahi’, ‘Ronga Bao’, ‘Bangali  Lahi’ and ‘Suwag Moni Horu’ could successfully be germinated and  established under anoxic condition.
Keywords: Anoxia; amylase activities; coleoptiles; genotypes; germination; rice; stress tolerance